Терапія телят за неспецифічної бронхопневмонії та її профілактика з використанням біогенних елементів і ехінацеї пурпурової - Дробот, Марина Вікторівна (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня кандидата ветеринарних наук зі спеціальності 16.00.01 «Діагностика і терапія тварин». Національний університет біоресурсів і природокористування України. Київ, 2021. У дисертації теоретично та експериментально обґрунтовано індивідуальний і груповий методи лікування телят за неспецифічної бронхопневмонії та її профілактика з використанням комплексного препарату «Кальфмін» на основі біогенних сполук наноаквахелатів і настою ехінацеї пурпурової. Досліджено показники природної резистентності телят за неспецифічної бронхопневмонії. Виявлено імунодефіцитний стан у хворих тварин – зниження активності клітинних і гуморальних факторів захисту організму. Доведено, що застосування телятам за неспецифічної бронхопневмонії препарату «Кальфмін» дає позитивний лікувальний ефект завдяки наявності у його складі сполук наноаквахелатів та ехінацеї пурпурової. Результатами проведених досліджень доведено позитивний вплив препарату «Кальфмін» на стан природної резистентності новонароджених телят, що сприяє профілактиці бронхопневмонії. Отримані результати досліджень підтверджують вищу терапевтичну ефективність від застосування препарату «Кальфмін» груповим аерозольним методом під час лікування хворих на бронхопневмонію телят, оскільки лікарський засіб надходить в організм тими ж шляхами, що і збудники хвороби.
The dissertation thesis for the scientific degree of the Сandidate of Veterinary Science, specialty 16.00.01 «Diagnosis and therapy of animals». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2021. In the dissertation work, the individual and group method of treatment and prevention of calves for nonspecific bronchopneumonia using the complex preparation Kalfmin based on biogenic compounds of nanoaquachelates and tincture of Echinacea purpurea is theoretically and experimentally substantiated. To determine the real situation on the pathology of respiratory diseases in calves, their development and distribution on the basis of the dispensary examination of the herd, the factors contributing to the occurrence of nonspecific bronchopneumonia in the farm have been clarified. According to the results of the analysis of the dispensary examination, the indicators of natural resistance of calves with nonspecific bronchopneumonia were investigated. An immunodeficiency state was revealed in sick animals: a decrease in the activity of cellular and humoral factors of the body's defense, a violation of the metabolism of proteins, lipids and carbohydrates. The studies carried out prove that the mass occurrence of nonspecific bronchopneumonia in the calves of the farm coincides with the period of regrouping of animals and their formation into a rearing group. As a rule, these were calves of 1.5–2 months of age, among which experimental and control groups were formed. The clinical state (body temperature, the number of respiratory movements and heart contractions per minute, the state of the mucous membranes, skin, lymph nodes), morphological blood parameters (the number of erythrocytes, leukocytes, platelets, blood leukogram, hematocrit blood count) and blood biochemical parameters (the content of hemoglobin in the blood, and in the blood serum – the content of total protein, albumin, globulins, glucose, cholesterol, triglyceride, lipoproteins). It has been established that the complex of the main etiological factors of the emergence and development of nonspecific bronchopneumonia of calves in a modern high-tech enterprise for the production of milk includes technological and anthropogenic factors that are difficult or impossible to avoid when regrouping young animals, causes stress on them, as well as a change in the diet, insufficient or the complete absence of technological solutions to prevent colds (crowding of animals, high humidity, partly below the standard values of the room air temperature, etc.) at which the conditionally pathogenic microflora of the respiratory tract of calves acquires pathogenicity and contributes to the development of a pathological process, which is the leading etiological factor and affects the nature of the inflammatory process, the course of the disease and its consequences. It has been proved that a complex of biogenic macro- and microelements (Copper, Iodine Argentum, Cobalt) and Echinacea purpurea, in an appropriate composition, in laboratory conditions suppresses the growth of opportunistic microflora found in patients with nonspecific bronchopneumonia of calves. On the basis of a complex of biogenic macro- and microelements (Copper, Iodine Argentum, Cobalt) and Echinacea purpurea, a complex preparation «Kalfmin» has been developed for individual oral therapy, group therapy with the aerosol method of calves with nonspecific bronchopneumonia and group prevention of this pathology in them. It has been shown that the use of «Kalfmin» by the method of individual therapy of calves with nonspecific bronchopneumonia already on the seventh day is characterized by a significant decrease in the number of stab neutrophils, segmented neutrophils in the blood and an increase in the number of eosinophils, with a simultaneous increase in the number of lymphocytes. It has been proven that the use of the «Kalfmin» drug stimulates an increase in the protein-synthesizing function of the liver of calves, which is characterized by a significant increase in the content of total protein and protein fractions in the blood serum of calves. The use of the «Kalfmin» drug contributed to an increase in the number of erythrocytes and hemoglobin in the blood of calves with bronchopneumonia, which is a sign of a stimulating effect on the adaptive mechanisms of the body in a state of hypoxia and hypoxemia, which develop during lung disease. It has been proven that the use of the «Kalfmin» drug contributes to a positive therapeutic effect from the use of compounds of nanoaquachelates and Echinacea purpurea for nonspecific bronchopneumonia of calves. As a result of the studies, the positive effect of the «Kalfmin» drug on the state of natural resistance of newborn calves has been proved, which contributes to the prevention of bronchopneumonia. The obtained research results confirm the high therapeutic efficacy of the «Kalfmin» drug by the group aerosol method in the treatment of calves with bronchopneumonia, since the drug enters the body in the same ways as the causative agents of the disease.
Keywords: телята; неспецифічна бронхопневмонія; клінічні показники; білок загальний; альбуміни; глобуліни; природна резистентність; препарат «Кальфмін»; calves; nonspecific bronchopneumonia; clinical parameters; total protein